Right to clean and unpolluted air in Nigeria (2020)
Right to clean and unpolluted air is a right recognised worldwide as part of human rights. The right has been incorporated into several countries’ constitutions and legislations apart from its recognition in the United Nations Conventions and other treaties. Although, the right to clean air is not expressly codified in Nigeria save legislations for the control ofpollution generally. This paper therefore examines the status of right to clean air in Nigeria. The objective of the paper is to stir up government to enact separate law for the enforcement of right to clean air. The paper adopts doctrinal approach to legal research as sources of its information. The paper finds that institutional constraints have rendered ineffective laws and regulations for the control of air pollution in Nigeria. The paper observes that right to clean air is universal right and argues for the enactment of Clean Air Act in Nigeria has done in other climes to create platform for the enforcement of right to clean air. The paper concludes with recommendation among others for stiffer penalty against Polluters of air and their collaborators in and outside government in Nigeria.